Staging language in Bermuda: phonology and parodic performance of Bermudian English - Hall, R (2018)
This thesis examines the link between social conditions and linguistic practice in Bermuda, a British Overseas Territory in the North Atlantic Ocean. Bermuda is an under-studied, often misunderstood context, home to a unique dialect of English which is under-represented in the literature on Lesser-Known Varieties (LKVEs). It is also an unusual, not-quite-post-colonial, ‘offshore’ setting with an unusual immigration pattern to match, which has led to intense debates about the meaning of national identity and ‘authentic’ Bermudian-ness. These debates are, inevitably, related to and reflected in language. This thesis argues that Black Bermudian English (BBerE) is a sub-variety of BerE arising from a history of enslavement, segregation and socioeconomic inequality, and goes on to show that BBerE is both mocked and simplified in parodic dialect performances, both written and spoken, common among white Bermudian men. The first part of the thesis gives a phonological overview of BBerE, and introduces Bermuda as a sociolinguistic setting, providing a foundation for further analyses of the variety. The second part focuses on various forms of dialect performance among a white male community of practice well-known for theatrical stylisations of BerE. Qualitative and quantitative analyses of performances which occurred during sociolinguistic interviews find them to be a form of racialised mock language. Contextual analysis shows that they construct a caricature with socially undesirable tastes, skills, and habits, and link these qualities to salient features of BBerE. Sociophonetic analysis compares the pronunciations of phonological variables among black and white speakers, and finds that white speakers’ performances target black variants missing from their own repertoire, while failing to produce the same complex patterning found in the black group. The speakers interviewed for this thesis overtly express the view that their performances represent legitimate self-parody, based on the idea that all Bermudians are immigrants from somewhere or another; ‘there’s no such thing as a native Bermudian.’ I argue, however, that the performances themselves reveal contradictions in this ideology. A ‘colourblind’ political stance is invoked to justify the appropriation of a black variety which the performers do not themselves speak, and which they deploy in ways that reproduce racist stereotypes; at the same time this appropriation is motivated by an essentialist idea of black Bermudian speakers as being ‘authentic’ in a way white speakers are not. The thesis introduces a wealthy island context to the literature on racialised dialect parody, prompting further investigation into privileged peripheries like Bermuda and advocating a nuanced and particularistic approach to the difficult sociolinguistic problem of authenticity.